Implant Distribution in Surgically Instrumented Lenke 1 Adolescent Idiopathic Scoliosis. Issue 7 (1st April 2015) - Le Navéaux, Franck; Aubin, Carl-Éric; Larson, A. Noelle; Polly, David W.; Baghdadi, Yaser M. K.; Labelle, Hubert
<x xml:space="preserve">Abstract</x> Study Design. Retrospective review of prospective multicenter database of patients with adolescent idiopathic scoliosis who underwent posterior spinal fusion. Objective. To analyze implant distribution in surgically instrumented Lenke 1 patients and evaluate how it impacts curve correction. Summary of Background Data. Although pedicle screw constructs have demonstrated successful surgical results, the optimal pedicle screw density and configuration remain unclear. Methods. A total of 279 patients with adolescent idiopathic scoliosis treated with pedicle screws were reviewed. Implant density was computed for each side of the instrumented segment, which was divided into 5 regions: distal and proximal ends (upper/lower instrumented vertebra +1 adjacent vertebra), apical region (apex ± 1 vertebra), and the 2 regions in between (upper/lower periapical). Centralized measurement of Cobb angle and thoracic kyphosis was performed on preoperative and at 1-year postoperative radiographs as well as percent curve flexibility. Results. The mean implant density was 1.66 implants per level fused (1.08 to 2) with greater available pedicles filled on the concavity (92%, 53%–100%) compared with the convex side (73%, 23%–100%, P < 0.01). The concave distal end region had the highest density with 99% of pedicles filled (P < 0.01), followed by the other concave regions and the convex distal end region (88%–94%) (P > 0.05). Other convex regions of the construct had less instrumentation, with only 54% to 78% of pedicles instrumented (P < 0.01). Implant density in the concave apical region (69%, 23%–100%) had a positive effect on curve correction (P = 0.002, R = 0.19). Conclusion. Significant variability exists in implant distribution with the greatest variation on the convex side and lowest implant density used in the periapical convex regions. Only instrumentation at the concave side, particularly at the apical region, was associated with curve correction. This suggests that for a low implant density construct, the best regions for planned screw dropout may be in the periapical convexity. Level of Evidence: 3